Reflection on Family-Centered Practices From the Perspective of Students of Physical Therapy, Occupational Therapy, and Speech Therapy in the Southeast of Spain - Orcajada-Sánchez, Noelia (2020)
More and more early childhood professionals are basing their work on family-centered practices. The change in this professional practice means that when university teaching begins to address this matter, even if only occasionally, it generates significant doubts in students, who are more accustomed to outpatient practices. In this article, we analyze doubts raised by students when an early childhood professional team talked to them about these family-centered practices. These doubts were about cases studied in Physiotherapy, Occupational Therapy, and Speech Therapy programs from two different universities in southeastern Spain. Some teaching staff members in these degrees organized training actions on family-centered practices in their courses. Through a non-experimental, qualitative design with an observational methodology, we described the doubts raised by 196 students attending these training actions. We also collected the answers, agreed upon by a group of professionals of these practices, to each of these doubts. We understand that these are questions that may arise to professionals or students, given that the process they go through to understand and adopt family-centered practices is usually similar, so it is useful to know and disseminate them. Our results point to differences in the questions raised by students of the different programs; they may reflect differences in their clinical training and in the previous training received in early childhood programs. We defend the importance of this training in future graduates from these degrees that qualify them to work as early childhood professionals.